Penerapan Kode Etik Pustakawan di Dinas Perpustakaan dan Kearsipan Kota Medan - Khairani Sinaga, Asri; Titin Sumanti, Solihah; Riza, Faisal (Comit: Communication, Information and Technology Journal, 2024)
The purpose of this study was to find out how the application of the librarian's code of ethics at the Medan City Library and Archives Service. This research method uses a qualitative method with a descriptive approach. In this study, there were 6 informants who worked in the library as librarians by using purposive sampling. The object of this research is the Medan City Library and Archives Service. The collection techniques used are observation, interviews and documentation studies. The analysis technique used in this research is data reduction, data presentation and conclusion. The results of this study are that at the City Library and Archives Service the librarians have implemented the Librarian Code of Ethics from the basic attitudes of librarians and some librarian rules, Inhibiting and Supporting Factors from this research there are obstacles where there are some librarians who do not have a librarian background so that this becomes an inhibiting factor in implementing the Librarian Code of Ethics in which there are some librarians who do not participate in the Indonesian Librarians Association, while the supporting factors for the Implementation of the Librarian Code of Ethics with the management of librarians are able to apply because they understand well the existing rules. Keywords: Librarian, Librarian Code of Ethics.